Influence of some factors on the arsenic adsorption by the nanosized MnO2 - Dai, Luu Minh; To Loan, Nguyen Thi (Vietnam Journal of Chemistry, 2012)
Nanosized MnO2 is potential sorbent for arsenic removal in drinking water. In this report we present the results of a detailed study on the effects of pH, temperature and the presence of cations, anious on arsenic adsorption by nanosized oxide MnO2.